Performance Pressure as an Antecedent and Authentic Leadership as a Moderator of the Relationship Between Co-worker Undermining and Psychological Capital - Jang, Eunmi; Kim, Hyunkoo (Frontiers in Psychology, 2021)
As a component of organizational aggression, co-worker undermining erodes the well-being of the victims and the sustainability of the organization. Drawing on conservation of resources theory, this study identified the negative impact of co-worker undermining on the victim's psychological capital and empirically examined the influence of performance pressure as an antecedent and of authentic leadership as a moderator to suggest approaches to minimize this negative impact. A total of 485 subordinate employees from 10 organizations in South Korea completed a questionnaire survey. To prevent common method bias, the survey was designed to recruit participants from multiple organizations and conducted in two waves. First, the results revealed that performance pressure had a positive relationship with the perception of co-worker’s undermining. Second, this perception of co-worker undermining had a negative influence on the victim’s psychological capital. Third, authentic leadership had the moderating effect of decreasing the negative relationship between co-worker undermining and psychological capital. These findings suggest that the level of performance pressure should be managed in advance to not reach excessive levels and the psychological capital of victims preserved through authentic leadership to minimize the negative impact of co-worker undermining.